2021
DOI: 10.1371/journal.ppat.1010018
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between coxsackievirus B3 infection and α-synuclein in models of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative diseases. PD is pathologically characterized by the death of midbrain dopaminergic neurons and the accumulation of intracellular protein inclusions called Lewy bodies or Lewy neurites. The major component of Lewy bodies is α-synuclein (α-syn). Prion-like propagation of α-syn has emerged as a novel mechanism in the progression of PD. This mechanism has been investigated to reveal factors that initiate Lewy pathology with the aim of preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Coxsackievirus B3 infection can induce α-synuclein-associated inclusion body formation in neurons, which might act as a trigger for PD. Transgenic mice that express α-synuclein showed enhanced Coxsackievirus B3 replication and exhibited dopaminergic neuronal death in the substantia nigra ( 30 ). A B-cell receptor signaling pathway and one carbon pool by folate signaling pathways were positively correlated with the DLB subset.…”
Section: Discussionmentioning
confidence: 99%
“…Coxsackievirus B3 infection can induce α-synuclein-associated inclusion body formation in neurons, which might act as a trigger for PD. Transgenic mice that express α-synuclein showed enhanced Coxsackievirus B3 replication and exhibited dopaminergic neuronal death in the substantia nigra ( 30 ). A B-cell receptor signaling pathway and one carbon pool by folate signaling pathways were positively correlated with the DLB subset.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the neuronal expression of alpha-synuclein is still unknown, but there is data suggesting alpha-synuclein expression in neurons is a restriction factor, inhibiting viral replication in the CNS [ 69 ]. In contrast, a recent study demonstrated that alpha-synuclein enhanced picornavirus replication in an experimentally infected PD mouse model, resulting in lower survival rate [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study found that α-synuclein is up-regulated and associated with α-synuclein inclusion body formation and dysfunctional autophagy machinery in neurons during coxsackievirus B3 (CVB3) infection. 51 Additionally, the authors observed α-synuclein aggregates in the cell body of midbrain neurons of mice infected with CVB3. 51 These modifications might act as triggers for PD.…”
Section: The Role Of Enterovirus Infection In Neurodegenerative Diseasesmentioning
confidence: 97%